Strategic Applications of Nanomaterials as Sensing Platforms and Signal Amplification Markers at Electrochemical Immunosensors. Issue 8 (25th May 2016) - Huo, Xiaohe; Liu, Xiaoqiang; Liu, Jin; Sukumaran, Preethi; Alwarappan, Subbiah; Wong, Danny K. Y.
Abstract: Tremendous developments in electrochemical immunosensors have facilitated cost‐effective, rapid and robust detection of many analytes. Among the significant developments, electrochemical immunosensors capable of simultaneously detecting several analytes have begun to emerge. In addition, recent progress in materials science and engineering has yielded nanostructured materials of various geometries that were readily exploited to provide a compatible medium for many biomolecules in immunoassays. Applications of these nanostructured materials to electrochemical immunosensor developments have significantly improved sensor performance in terms of their electrical, chemical and transport properties. This review provides a survey of innovative immunosensor developments involving a range of nanomaterials exploited in designing sensing platforms and efficient detection markers to achieve substantial signal amplifications and thereby outstanding detection characteristics. Abstract :